The Integrated Role of BKK and BKK in Preparing Vocational Students to Work: Peran Terintegrasi BKK dan BK dalam Menyiapkan Siswa SMK Bekerja - Khomsah, Nur Lina; Suryadi, Tri; Yayuk, Erna (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: In the context of the Industrial Revolution 4.0, vocational education plays a strategic role in preparing skilled, competitive, and job-ready graduates. Specific Background: However, SMK graduates in Indonesia still face high unemployment rates, indicating a gap between education and labor market demands. Knowledge Gap: Previous studies have examined Special Job Exchange (BKK) and Counseling Guidance (BK) separately, but few have explored their integrated contribution to students’ job readiness. Aims: This study aims to investigate the synergy between BKK and BK services in enhancing the job readiness of vocational students. Results: Using a qualitative case study at SMKN 1 Nguling, Pasuruan, the research found that BKK facilitates job matching, soft skills training, and industry collaboration, while BK supports career planning, self-confidence, and mental preparation. Their integration positively affects students’ technical competencies, communication, work ethic, and psychological readiness. Novelty: This research offers new insights into the integrated role of BKK and BK in a semi-rural vocational school context, highlighting unique collaborative models. Implications: The findings provide empirical evidence for policymakers and educators to design school-to-work transition programs that are structurally collaborative and contextually relevant for vocational education enhancement.Highlight : Integration of BKK and BK significantly improves students' job readiness through collaborative programs and career planning. SMKN 1 Nguling shows effective models in job matching, soft skills training, and tracer studies with a 97% graduate absorption rate. The study highlights the importance of aligning student interests with industry demands through structured guidance and counseling. Keywords : Special Job Exchange, Counseling Guidance, Job Readiness, Vocational Students, SMK